2017
DOI: 10.3389/fpls.2017.01094
|View full text |Cite
|
Sign up to set email alerts
|

Root Hair Mutations Displace the Barley Rhizosphere Microbiota

Abstract: The rhizosphere, the thin layer of soil surrounding and influenced by plant roots, defines a distinct and selective microbial habitat compared to unplanted soil. The microbial communities inhabiting the rhizosphere, the rhizosphere microbiota, engage in interactions with their host plants which span from parasitism to mutualism. Therefore, the rhizosphere microbiota emerges as one of the determinants of yield potential in crops. Studies conducted with different plant species have unequivocally pointed to the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
94
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 47 publications
14
94
0
Order By: Relevance
“…Although these findings were gathered from the individual soil tested and further validation across a range of soil types is required, a prediction from these observations is that the host control of the rhizosphere microbiota is exerted by a limited number of loci in the genome with a relatively large effect. This is congruent with our previous observation that mono-mendelian mutations in a single root trait, root hairs, impact on ~18% of the barley rhizosphere microbiota 25 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although these findings were gathered from the individual soil tested and further validation across a range of soil types is required, a prediction from these observations is that the host control of the rhizosphere microbiota is exerted by a limited number of loci in the genome with a relatively large effect. This is congruent with our previous observation that mono-mendelian mutations in a single root trait, root hairs, impact on ~18% of the barley rhizosphere microbiota 25 .…”
Section: Discussionsupporting
confidence: 93%
“…The distribution of reads assigned to given phyla appears distinct in plant-associated communities which are dominated in terms of abundance by members of the phyla Acidobacteria, Actinobacteria, Bacteroidetes and Proteobacteria , with these two latter phyla significantly enriched in rhizosphere samples compared to bulk soil controls. This taxonomic affiliation is consistent with previous investigations in barley in either the same 25 or in a different soil type 15 as well as in other crop plants 26 . In summary, these data indicate that the higher taxonomic ranks of the barley rhizosphere microbiota are conserved across soil types as well as wild and domesticated genotypes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the bacterial community was dominated by members of the Proteobacteria phylum, with remarkably high abundance of a single bacterium belonging to the γ‐proteobacteria and classified as Candidatus Nardonella. These findings are consistent with those reported previously in insect bacterial community studies, which revealed a similarly low diversity of bacterial microbiota dominated by members of the Proteobacteria phylum, compared with analogous studies on vertebrates or soil (Broderick et al., ; Fierer & Jackson, ; Vasanthakumar et al., ; Corby‐Harris et al., ; Chandler et al., ; Douglas, ; Ishak et al., ; Wong et al., ; Colman et al., ; Jones et al., ; Bansal et al., ; Yun et al., ; Gauthier et al., ; Bili et al., ; Robertson‐Albertyn et al., ). This bacterial microbiota pattern seems to be common across insect clades even when targeting different 16S rRNA gene hypervariable regions (Suzuki & Giovannoni, ; Baker et al., ; Guo et al., ; Yang et al., ) or applying different DNA extraction procedures (Martin‐Laurent et al., ).…”
Section: Discussionsupporting
confidence: 91%